Клинический опыт применения метода конусно-лучевой компьютерной томографии в эндодонтии (Эндодонтия Today, 2020)
The most important step in the work of endodontist is an appropriate diagnostics. For effective diagnosis and subsequent endodontic treatment standard methods of dental x-ray and planar radiography are not enough. Currently, scientists and clinicians discussed the role of cone-beam computed tomography (CBCT) in the diagnosis of apical periodontitis (AP). In this paper in a series of case reports the use of CBCT for diagnosis and monitoring treatment success is described. The authors discuss the topic of the higher efficacy of CBCT for diagnosis of the condition surrounding the tooth structures in the apical lesions. The use of standard planar radiographs in these cases is compared with CBCT.